Training factors and its impact on training effectiveness in Petronas Carigali Sdn. Bhd. Miri, Sarawak (PCSB SK OIL) / Shazlinda Sulaiman Ng - Sulaiman Ng, Shazlinda (Faculty of Business and Management, 2018)
In Malaysia so many enterprise implement various training to enhance their employees by working performance. But as overall view, the training environment still exist shortages in enterprise today, for instance, lack of knowledge of training, resources, trainer and others. Employee training has been a matter of concern and attention by many business fields nowadays. Organizations realize that employee training is an essential element to increase efficiency in job performance and keep their business running, as competition are getting more intense. Training is the process of providing employees with specific skills or helping them to correct deficiencies in their performance (David, 2010). This study, combining theoretical and empirical research trying to find factors that affect employee training and impact in acting human resource practices thereby laying the theoretical foundation for the future research about survey on the employee training, also provide a good reference. Therefore, the problem addressed in this study is to determine the level of training effectiveness in Petronas Carigali Sdn. Bhd. Miri, Sarawak. This research also determine the factors affect training effectiveness (training participant characteristics, training environment and work environment) in the stated company and also the most critical factor that influence training effectiveness. Management is committed to human resource development as well as its social responsibilities through various programs. Training and development program are offered by the PCSB SK Oil that training program also adapted to the latest technology advances.